Pengaruh Permainan Tradisional Pecle Terhadap Kekuatan Menendang Bola Di SDN Leuwipicung - Mochammad Rizwan; Rahmat Permana; Mohammad Fahmi Nugraga (Publikasi Indonesia, 2022)
There are various types of sports, one of which is soccer. Almost all people in the world know this sport, even though they don't like it or don't play it, at least most people in the world know this type of sport. The goal of soccer is to score as many goals as possible against the opponent's goal. To be able to score a goal must be able to kick the ball well. To improve students' kicking skills, the way to do this is by using the traditional game of pecle. The goal to be achieved is to determine the effect of the traditional pecle game on the kick strength of students who take part in soccer extracurriculars at SDN Leuwipicung. In this study, the researchers used a quasi-experimental posttest only control group design. The population in this study were 25 students of SD Negeri Leuwipicung who took part in extracurricular football. In this study, the researchers used a saturated sampling technique because the population was less than 30 people. Data were obtained using interviews, observation, practical tests and documentation. The test used is kicking for distance from warner test of soccer skill. The results of the reliability test using Cronbach's Alpha with the result of 0.153. That way the reliability test gets reliable results because the Alpha value > 0.60. Based on the results obtained, the results of the research on the traditional game of pecle have an effect on kicking power in soccer.